Why and how do protective symbionts impact immune priming with pathogens in invertebrates?. (January 2022) - Prigot-Maurice, Cybèle; Beltran-Bech, Sophie; Braquart-Varnier, Christine
Abstract: Growing evidence demonstrates that invertebrates display adaptive-like immune abilities, commonly known as "immune priming". Immune priming is a process by which a host improves its immune defences following an initial pathogenic exposure, leading to better protection after a subsequent infection with the same – or different – pathogens. Nevertheless, beneficial symbionts can enhance similar immune priming processes in hosts, such as when they face repeated infections with pathogens. This "symbiotic immune priming" protects the host against pathogenic viruses, bacteria, fungi, or eukaryotic parasites. In this review, we explore the extent to which protective symbionts interfere and impact immune priming against pathogens from both a mechanical (proximal) and an evolutionary (ultimate) point of view. We highlight that the immune priming of invertebrates is the cornerstone of the tripartite interaction of hosts/symbionts/pathogens. The main shared mechanism of immune priming (induced by symbionts or pathogens) is the sustained immune response at the beginning of host-microbial interactions. However, the evolutionary outcome of immune priming leads to a specific discrimination, which provides enhanced tolerance or resistance depending on the type of microbe. Based on several studies testing immune priming against pathogens in the presence or absence of protective symbionts, we observed that both types of immune priming could overlap and affect each other inside the same hosts. As protective symbionts could be an evolutionary force that influences immune priming, they may help us to better understand the heterogeneity of pathogenic immune priming across invertebrate populations and species. Highlights: Immune priming is a cornerstone of the interaction hosts/symbionts/pathogens. Both symbionts and pathogens induce sustained immune responses in hosts. Symbiotic and pathogenic immune priming may interfere in the same host. Symbionts could be a selective force that influences pathogenic immune priming. Symbiotic immune priming may help us to better understand pathogenic immune priming.